HCBS Service Spending and Nursing Home Placement for Patients With Alzheimer's Disease and Related Dementias: Does Race Matter?. (March 2022) - Yan, Di; Wang, Sijiu; Temkin-Greener, Helena; Cai, Shubing
Objectives: We examined the extent to which home and community-based services (HCBS) spending affected the likelihood of nursing home (NH) placement among black and white HCBS users with Alzheimer's disease and related dementias (ADRD). Methods: The study population included new HCBS users with ADRD between 2010 and 2013 ( N = 1, 046, 200). Results: We found that a one hundred dollar increase in monthly HCBS spending was associated with a 0.3 percentage points decrease in the NH placement rate among Whites, but a 0.3 percentage points increase in the NH placement rate among Blacks. The overall NH placement rate was 68.2% and 56.7% for Whites and Blacks, respectively. Discussion: A higher HCBS spending was associated with a decreased likelihood of NH placements for Whites but not for Blacks. It is important to understand how states' HCBS expansion efforts influence Blacks and Whites with ADRD so that resources can be tailored to communities with different race-mix.